3(y+6)-y=2(y-9)

Simple and best practice solution for 3(y+6)-y=2(y-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y+6)-y=2(y-9) equation:


3(y+6)-y=2(y-9)

We simplify the equation to the form, which is simple to understand
3(y+6)-y=2(y-9)

Reorder the terms in parentheses
+(+3y+18)-y=2*(y-9)

Remove unnecessary parentheses
+3y+18-y=+2+*(+y-9+)

Reorder the terms in parentheses
+3y+18-y=+(+2y-18)

Remove unnecessary parentheses
+3y+18-y=+2y-18

We move all terms containing y to the left and all other terms to the right.
+3y-1y-2y=-18-18

We simplify left and right side of the equation.
y=-36

0=-36

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 2(5-x)=4x | | (2x+5)(4x-2)=(2x)(4x) | | (2x+5)(4x-2)=(2x)(4x)+(2x)(-2)+(5)(4x)+(5)(-2) | | -15x^2+11x-2=0 | | 12x^2+13x-30=0 | | 6x^2-11x+2=0 | | ln(x)-ln(x-7)=ln(2) | | ln(x)-ln(x-7)=ln(2) | | 30r^2-13r-3=0 | | 30t^2-49t+20=0 | | 589270957349857476-4= | | 12x^2+5-23x=0 | | 3(4x+5)=63 | | 5x^2-6x+4=0 | | 3a+8=20 | | 2a+9=17 | | a+1=4 | | X(3)=12 | | 16x-8y=64 | | 4(3q+7)=7 | | 7x+38=-4 | | 11(16-g)=22 | | f=-2f-9 | | -84-8x=9x+18 | | 156-7x=29x+24 | | 145-6x=3x+10 | | 8f=-2f-10 | | 9x=125 | | 2a+12=6 | | 7x=-64 | | 7x+32=-32 | | x=5000 |

Equations solver categories